Morphology, chemical interaction, and conductivity of a PEO-ENR50 based on solid polymer electrolyte - Noor S.A.M.; Ahmad A.; Talib I.A.; Rahman M.Y.A. (2023)
A solid polymer electrolytes (SPE) comprising blend of poly(ethylene oxide; PEO) and epoxidized natural rubber as a polymer host and LiCF3SO3 as a dopant were prepared by solution-casting technique. The SPE films were characterized by field emission scanning electron microscopy to determine the surface morphology, X-ray diffraction, and differential scanning calorimeter to determine the crystallinity and thermogravimetric analysis to confirm the mass decrease caused by loss of the solvent. While the presence of the complexes was investigated by reflection Fourier transform infrared (ATR-FTIR) spectroscopy. Electrochemical impedance spectroscopy was conducted to obtain ionic conductivity. Scanning electron microscopy analysis showed that a rough surface morphology of SPE became smoother with addition of salt, while ATR-FTIR spectroscopy analysis confirmed the polymer salt complex formation. The interaction occurred between the salt, and ether group of polymer host where the triple peaks of ether group in PEO merged and formed one strong peak at 1,096 cm-1. Ionic conductivity was found to increase with the increase of salt concentration in the polymer blend complexes. The highest conductivity achieved was 1.4 10-4 Scm-1 at 20 wt.% of LiCF3SO3, and this composition exhibited an Arrhenius-like behavior with the activation energy of 0.42 eV and the preexponential factor of 1.6 103 Scm-1. Springer-Verlag 2009.